Collusion in the Bertrand-Cournot model : analysing strategic behaviour and market outcomes - Martins, Beatriz de Almeida (2024)
This dissertation examines the sustainability of collusion in a Cournot-Bertrand model involving three firms, where the strategic variable (price or quantity) is chosen before competition or collusion begins. Using the Singh and Vives (1984) demand model, the analysis considers both full and partial collusion, focusing on the role of a third firm that always competes independently. The critical discount factor is used to assess the ease of sustaining collusion under various scenarios. Results show that collusion is more stable when firms compete on quantities due to softer competition, while price-setting firms face stronger incentives to deviate. In mixed strategy scenarios, where some firms set prices and others set quantities, collusion becomes harder to maintain. The degree of product substitution also plays a crucial role, with higher substitution making collusion more fragile. For partial collusion, stability is greater when the third firm competes on price rather than quantity. The findings highlight the complexity of maintaining collusion in hybrid Cournot-Bertrand environments and suggest that coordination is easier when firms align their strategic variables. The dissertation also suggests potential extensions, including analyzing deviations by the third firm and assessing the impact on consumer welfare.